Does Delayed Pushing in the Second Stage of Labor Impact Perinatal Outcomes? - Frey, Heather A.; Tuuli, Methodius G.; Cortez, Sarah; Odibo, Anthony O.; Roehl, Kimberly A.; Shanks, Anthony L.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2012)
Objective To estimate maternal, neonatal, and labor outcomes associated with delayed pushing.Study Design A retrospective cohort study of all consecutive women admitted to a single institution in labor at term who reached the second stage of labor. Pregnancies with multiple fetuses or major anomalies were excluded. Delayed pushing was defined as initiation of pushing ≥60 minutes after complete dilatation. Primary outcome was mode of delivery. Multivariable logistic regression was used to control for confounding.Results Of the 5290 women who met inclusion criteria, 471 (8.9%) employed delayed pushing, and 4819 (91.1%) pushed immediately. Delayed pushing was associated with increased rates of cesarean, operative vaginal delivery, maternal fever, and lower arterial cord pH. Duration of the second stage and length of time spent pushing were significantly longer with delayed pushing.Conclusion Delayed pushing is associated with lower rates of spontaneous vaginal delivery and increased adverse maternal and neonatal outcomes.
Keywords: delayed pushing; labor management; second stage